The multi-omic landscape of sex chromosome abnormalities: current status and future directions - Helene Bandsholm Leere Tallaksen; Emma B Johannsen; Jesper Just; Mette Hansen Viuff; Claus H Gravholt; Anne Skakkebæk (Endocrine Connections, 2023)
Sex chromosome abnormalities (SCAs) are chromosomal disorders with either a complete or partial loss or gain of sex chromosomes. The most frequent SCAs include Turner syndrome (45,X), Klinefelter syndrome (47,XXY), Trisomy X syndrome (47,XXX), and Double Y syndrome (47,XYY). The phenotype seen in SCAs is highly variable and may not merely be due to the direct genomic imbalance from altered sex chromosome gene dosage but also due to additive alterations in gene networks and regulatory pathways across the genome as well as individual genetic modifiers. This review summarizes the current insight into the genomics of SCAs. In addition, future directions of research that can contribute to decipher the genomics of SCA are discussed such as single-cell omics, spatial transcriptomics, system biology thinking, human-induced pluripotent stem cells, and animal models, and how these data may be combined to bridge the gap between genomics and the clinical phenotype.